Acrocarpospora catenulata sp. nov., a novel actinobacterium isolated from lake sediment. Issue 9 (21st September 2022) - Liu, Chaolan; Guo, Yidong; Li, Li; Li, Jianghua; Wang, Limei; Lin, Jiafu; Wang, Xinrong; Chu, Yiwen
Abstract : A novel actinobacterium, designated strain H8750 T, was isolated from sediment sampled at Lugu Lake, southwest PR China and its polyphasic taxonomy was studied. Strain H8750 T produced well-developed substrate mycelium, and formed club-shaped and hooked structures borne on the tip of the aerial mycelia. It contained meso -diaminopimelic, glucose, ribose and madurose in whole-cell hydrolysates. The predominant menaquinones were MK-9(H4 ), MK-9(H2 ) and MK-9(H6 ). The phospholipid profile contained diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, hydroxy-phosphatidylethanolamine, unidentified phospholipids and unidentified aminophospholipids. The major fatty acid (>10 %) were cis 9 C17 : 1, iso-C16 : 0 and C15 : 0 . The DNA G+C content was 69.7 mol% based on the whole genome sequence. Phylogenetic analysis based on 16S rRNA gene and whole-genome sequences indicated that strain H8750 T was closely related to Acrocarpospora macrocephala JCM 10982 T (98.0 %), Acrocarpospora pleiomorpha JCM 10983 T (97.9 %) and Acrocarpospora phusangensis DSM 45867 T (97.8 %) and formed a monophyletic clade within the genus Acrocarpospora in the phylogenetic trees. The average nucleotide identity and digital DNA–DNA hybridization values between strain H8750 T and its closely related Acrocarpospora species were 79.8~87.2 % and 25.9~28.0 %, respectively, which showed that it belonged to a distinct species. Furthermore, the morphological and phenotypic characteristics allowed the isolate to be differentiated from its closely related species. Therefore, it is concluded that strain H8750 T can be classified as representing a novel species of the genus Acrocarpospora, for which the name Acrocarpospora catenulata sp. nov. is proposed. The type strain is H8750 T (=JCM 34849 T =CICC 25116 T ). Moreover, based on the gene prediction results, strain H8750 T may have the genetic potential to synthesize many new secondary metabolites, which further increases its bioactive value.